Subrata Roy Chowdhury, The Genesis of Bangladesh, A Study in International Legal Norms and Permissive Conscience, Asia Publishing House; Nueva York, 1972. 345 pp. - Susana B. C. Devalle (El Colegio de México, A.C., 1972)
-